Constraining the inclination of the low-mass X-ray binary Cen X-4. Issue 4 (22nd May 2018) - Hammerstein, Erica K; Cackett, Edward M; Reynolds, Mark T; Miller, Jon M
ABSTRACT: We present the results of ellipsoidal light-curve modelling of the low-mass X-ray binary Cen X-4 in order to constrain the inclination of the system and mass of the neutron star. Near-IR photometric monitoring was performed in 2008 May over a period of three nights at Magellan using PANIC. We obtain J, H, and K light curves of Cen X-4 using differential photometry. An ellipsoidal modelling code was used to fit the phase folded light curves. The light-curve fit that makes the least assumptions about the properties of the binary system yields an inclination of $34.9^{+4.9}_{-3.6}$ deg (1σ), which is consistent with previous determinations of the system's inclination but with improved statistical uncertainties. When combined with the mass function and mass ratio, this inclination yields a neutron star mass of $1.51^{+0.40}_{-0.55}$ M⊙ . This model allows accretion disc parameters to be free in the fitting process. Fits that do not allow for an accretion disc component in the near-IR flux give a systematically lower inclination between approximately 33 and 34 deg, leading to a higher mass neutron star between approximately 1.7 and 1.8 M⊙ . We discuss the implications of other assumptions made during the modelling process as well as numerous free parameters and their effects on the resulting inclination.